Stargazer [compact disc, unabridged] - Hillerman, Anne, 1949- (Hillerman, Tony Leaphorn and Chee novel, 2021)
What begins as a typical day for Officer Bernadette Manuelito, serving a bench warrant, dealing with a herd of cattle obstructing traffic, and stumbling across a crime scene, takes an unexpected twist when she's called to help find an old friend. Years ago, Bernie and Maya were roommates, but time and Maya's struggles with addiction drove them apart. Now Maya's brother asks Bernie to find out what happened to his sister. Tracing Maya's whereabouts, Bernie learns that her old friend had confessed to the murder of her estranged husband, a prominent astronomer. But the details don't align. Suspicious, Bernie takes a closer look at the case only to find that nothing is as it seems. Uncovering new information about the astronomer's work leads Bernie to a remote spot on the Navajo Nation and a calculating killer. The investigation causes an unexpected rift with her husband and new acting boss, Jim Chee, who's sure Bernie's headed for trouble.